UHPLC-QTOF-MS analysis of bioactive constituents from two Romanian Goji (Lycium barbarum L.) berries cultivars and their antioxidant, enzyme inhibitory, and real-time cytotoxicological evaluation. (May 2018) - Mocan, Andrei; Moldovan, Cadmiel; Zengin, Gökhan; Bender, Onur; Locatelli, Marcello; Simirgiotis, Mario; Atalay, Arzu; Vodnar, Dan Cristian; Rohn, Sascha; Crișan, Gianina
Abstract: Goji ( Lycium barbarum L.) berries are emphasized as healthy food or are used widely as dietary supplements. In the present study, the antioxidant and enzyme inhibitory activities of berries extracts from two selected Romanian cultivars (cv. Erma and cv. Biglifeberry) have been evaluated. UHPLC-QTOF-MS analysis results revealed the presence of organic acids, phenolic acids, flavonoids, fatty acids (oxylipins), and spermidine derivatives. In particular, cv. Erma showed an important tyrosinase-inhibitory effect, whereas, cv. Biglifeberry had a superior antioxidant capacity. Particularly, results provided by the CUPRAC assay showed the highest antioxidant capacity values (26.91 mg TE/g and 35.41 mg TE/g, for 'Erma' and 'Biglifeberry', respectively). Toxicological properties of the extracts were evaluated with human embryonic kidney cells (HEK-293) using the cytotoxicity analysis platform iCELLigence, real-time and label-free impedance technology. No cytotoxic effects were observed in a time- and dose-dependent manner. Overall, Goji berries are a rich source of bioactive compounds with functional properties that need further risk/benefit evaluation when used in foods or health-promoting formulations.